Quality of Life, Depression, Anxiety Symptoms and Mood State of Wheelchair Athletes and Non-athletes: A Preliminary Study - Vancini, Rodrigo Luiz; Gomes, Andressa Amato; de Paula-Oliveira, Hudson; de Lira, Claudio; Rufo-Tavares, Weverton; Andrade, Marilia Santos; Sarro, Karine Jacon; Sampaio, Martoni Moreira; Viana, Ricardo Borges; Nikolaidis, Pantelis Theodoros; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2019)
The present study aims to compare quality of life, depression, anxiety symptoms, and profile of mood state of wheelchair athletes and non-athletes. Thirty-nine basketball and rugby wheelchair athletes (n = 23, nine women, age 36.0 ± 10.0 years; body mass 66.2 ± 13.8 kg; height 170.0 ± 8.5 cm) and non-athletes (n = 16, 4 women, 39.0 ± 14.2 years; body mass 79.6 ± 17.2 kg; height 170.0 ± 6.4 cm) were recruited. Quality of life, anxiety and depressive symptoms and mood disorders were evaluated by the Medical Outcomes Short-Form Health Survey (SF-36), State-Trait Anxiety Inventory, Beck Depression Inventory and Profile of Mood State questionnaire, respectively. Comparison between groups (non-athletes vs. athletes) was performed using Student’s t-test for independent samples. No differences (p > 0.05) were found between non-athletes vs. athletes regards to quality of life, depressive and anxiety symptoms and profile of mood state. Overall, non-athletes and athletes presented medium anxiety symptoms and mild to moderate depressive symptoms. In conclusion, the wheelchair athletes and non-athletes presented similar quality of life, depressive and anxiety symptoms, and profile of mood state.